Components, Criteria and Indicators of the Readiness Levels of Future Naval Infantry Units Officers for Professional Activity - Ihor Zaitsev (Pedagogical Discourse, 2021)
The essence of components, criteria and indicators of the of the readiness levels of future naval infantry units officers for professional activities have been developed and revealed in the article. It is found out that the structure of readiness of future naval infantry units officers for professional activity consists of such components: personal and motivational (the criteria of this component motivational and orientation value orientations has been chosen, awareness of the necessity and goals of preparation for professional activity, the formation of a system of motives and values of the future specialist regarding future professional activity, which is accompanied by interest and desire to succeed in future professional activity), cognitive and content (criteria of knowledge – strength and depth of knowledge due to implementation of tasks and functions in future professional activities, a system of professional knowledge of the military field which is necessary for the effective implementation of educational and professional activities; the availability of special knowledge among cadets in professionally oriented disciplines), information and activity (criteria operational – abilities and skills to act in the conditions of future professional activity, the cadet’s ability to assess different situations, to make decisions about actions in different situations quickly and correctly), reflexive and creative (reflexive criteria – reflexive position, the ability to self-assessment, creative solution of various situations, the reflexive component is endowed with a self-regulating function and reveals skills and ability of cadets to evaluate the results of their own activities in the direction function of readiness to ensure safety in future professional activities, the care for the preservation of health and property values, to be able to reflect and correct their behavior, to strive for self-improvement and self-development).According to certain components, criteria and indicators, three levels of readiness of future naval infantry units officers for professional activity have been determined: high, medium and low.